PROCESS OPTIMISATION AND MICRONUTRIENTS RETENTION IN THE PRODUCTION OF OVEN-DRIED ORANGE FLESHED SWEET POTATO FLOUR: TIME STUDY AND VALUE STREAM MAPPING APPROACH - BABATUNDE O. ODEDAIRO; GIBSON L. ARUEYA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Orange Fleshed Sweet Potato (OFSP) is a highly nutritious tuber, rich in vitamins, and a major source of micronutrients (beta-carotene, ascorbic acid and phenolic acid). The retention of these micronutrients during the conversion of OFSP to flour is limited by the choice of drying methods. There is a dearth of information for ascorbic acid and phenolic acid retention levels. Therefore, this study was designed to optimise the OFSP processing methods so that appreciable quantities of the micronutrients are retained in the conversion of OFSP to flour. Time study and Value stream mapping methods were used to establish a standard time for each operation and process improvement, respectively. Using the traditional methods, production time for the process was 2 days, 2 hrs, 44 mins. For the optimised process, the production time was 9 hrs, 5 min, 15 s. The processed OFSP flour had the following nutrient densities: betacarotene (0.00011 mgꞏg-1), ascorbic acid (1.76120 mgꞏg-1), and phenolic acid (0.24321 mgꞏg-1) at optimised conditions. Based on these results, it can be concluded that nutrients were retained in good measure for the OFSP (Mother’s Delight Variety) through improved drying and production times.